The Top-Cited Original Articles on the Role of Microglia in Neurodegenerative Diseases: A Bibliometric and Visualized Study - Sun, Mengjiao; Li, Xiaoling; Sun, Jing; Wang, Hongxia; Xie, Qinfang; Wang, Manxia (Frontiers in Aging Neuroscience, 2022)
Background: Microglia participants to neuronal loss during brain development, inflammation, ischemia, and neurodegeneration. This bibliometric and visualized study aimed to confirm the top-100 cited original research in the field and to analyze the characteristics. Methods: The Web of Science database (WOS) was retrieved on February 21, 2022. The top 100 cited original articles that focused on the role of microglia in neurodegenerative diseases (NDs) were filtered by two researchers independently. The trend of yearly publications and citations, citation densities, languages, and global contributions were analyzed. The highly cited countries, authors, institutions, and journals were visualized by bibliographic coupling analysis. The highly cited authors and journals in the references were visualized by co-citation analysis. The research hotspots were revealed by co-occurrence analysis and burst detection of author keywords. Results: The top-100 cited articles were published during the period 1988 to 2019. The peak of publication occurred in 2005 and 2006. The yearly total citations presented a rising trend. The highly cited articles were contributed by 26 countries, the USA was the country with the overwhelming number of publications and cited times. Stevens, Beth was the author with the largest number of cited times. Mcgeer PL was the author most frequently cited in the references. Harvard University was the institution with the greatest number of cited times and publications. Nature was the journal with the largest number of cited times. Journal of neuroscience was both the most often published and most frequently cited journal in the references. “Microglia”, “inflammation”, “Alzheimer's disease” were the most frequently used keywords, and their average occurred time was around 2005. “Dementia”, “delirium”, “priming” were keywords that averagely occurred around 2010. The burst detection revealed that “TNF-beta”, “macrophage”, and “inflammation” were keywords that frequently burst in recent years. Conclusions: This bibliometric and visualized study revealed the top 100 cited original research that discussed the role of microglia in NDs. The USA was the biggest contributor, Harford University was the most influential institution. Journal of Neuroscience was the most often published and cited journal. Alzheimer's disease was the hotspot in microglia and NDs. Recent research mainly focused on inflammation.